The utility of peripheral stereopsis - Verghese, Preeti (Frontiers in Neuroscience, 2023)
This perspective article makes the case for evaluating and training peripheral stereopsis, particularly when the central visual field is compromised in one or both eyes. Examples of clinical conditions that preferentially affect the central visual field include macular degeneration, which affects the central macular region in one or both eyes, and amblyopia where the central field is often affected in one eye, but the peripheral field is largely intact. While binocular acuity may be preserved when the monocular central field of one eye is affected, fine stereopsis is compromised because it requires intact vision in corresponding locations in the two eyes. Even in these clinical conditions, recent studies that map stereoacuity at locations across the visual field demonstrate that the periphery supports coarse stereopsis, and that training efforts to use residual stereopsis may have greater benefit if they take this finding into account.